Knowledge of hypertensive patients and practice of pharmacists in the management of hypertension at the Dikgale Primary Health Clinics, Limpopo Province - Setshekgamollo, Masoto Mapula (My University, 2020)
Background: Non-communicable diseases (NCDs) which are chronic diseases in nature, have been the most common cause of death and disability globally for the last three decades. The prevalence of hypertension in South Africa has been estimated to be 20% of the adult population with over six million people being affected. Patient’s knowledge and awareness of blood pressure plays an important role in achieving successful control of hypertension. Although it is important for a physician to be involved in this educational process, pharmacists also have a role to play in this regard. Given their accessibility and drug therapy expertise, pharmacists are a logical choice and a valuable asset to improve hypertension management via team-based care and also when they are in direct consultation with the patients. Methods: The study involved both qualitative and quantitative research methods. A pre-validated questionnaire was used to collect data from 341 patients attending the 4 clinics at Ga-Dikgale. A semi-structured one-on-one interviews were used as data collection for 20 pharmacists working at Mankweng hospital until saturation was reached. Results: On the knowledge about definition, 30.7% were knowledgeable and 5.8% were highly knowledgeable. On the knowledge about treatment, 48% were highly knowledgeable. With regards to lifestyle modifications 77.8% were highly knowledgeable. For complications of hypertension, 63.2% were highly knowledgeable. Amongst the participants level of education proved to play a significant role on the knowledge of hypertension. The study also revealed that pharmacists shared similar practices in the management of hypertension. The following themes emerged from the data analysis, using Tesch’s inductive, descriptive coding technique of qualitative data analysis: Perceived roles of pharmacists during the management of hypertensive patients, expectations of pharmacists during provision of medication to hypertensive patients, and challenges related to pharmacists’ practices during care of hypertensive patient}s. Conclusions: The results of the quantitative study indicated that participants at Dikgale have good knowledge about hypertension, although previous studies indicate high rates of cardio-metabolic risk factors for hypertension. Further studies need to be conducted to determine reasons for patients not practicing lifestyle modifications. The results of the qualitative study indicated that there are common practices of pharmacists in the management of hypertension. More attention should be focused on training pharmacists on how to provide comprehensive counselling to hypertensive patients. There should also be workshops for pharmacists on how to efficiently educate patients on hypertension.
Thesis (M.Pharm.) -- University of Limpopo -- 2020
Keywords: Chronic diseases; Hypertension; Knowledge; Hypertension; Pharmacists -- South Africa -- Limpopo; Chronic diseases